Evaluation of Tahfidz Program Assessment at SMP Al-Fattah Tigaraksa (Evaluative Research using a Formative Evaluation Model) - Intani, Tita Kinasih; Aliep, Aliep (Universitas Sebelas Maret, 2024)
Assessment is one of the things that must be done to evaluate the learning process. The purpose of this research is to find out the aspects of assessment carried out by teachers, the assessment techniques used by teachers, and the procedures carried out by teachers in carrying out Tahfidz assessment. The method in this study uses a qualitative descriptive design (Formative Evaluation Model) to answer research questions. The sample used is class VIII B students of Al Fattah Junior High School as many as 5 students and 5 female students as purposive sampling. Data collection techniques in this study were interviews and document analysis. Data analysis was carried out with the following steps: Data deduction, data presentation, and verification and conclusion drawing. The results showed that the aspects of assessment that have been carried out by teachers include cognitive, psychomotor, and affective aspects; Assessment techniques developed by teachers are written and oral tests. While observation, portfolio, journal assessment, self-assessment, and peer assessment techniques have not been well developed. Assessment procedures carried out by teachers have not fully met the components as contained in the Tahfidz program.